Chickenpox Mimicking Monkeypox in Adult with Diabetes Mellitus and Acute Kidney Injury: Diagnosis and Management - Maya Wardiana; Rahmadewi Rahmadewi; Dwi Murtiastutik; Sawitri Sawitri; Damayanti Damayanti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Chickenpox caused by the varicella-zoster virus (VZV) in diabetes mellitus patients might exhibit similar clinical features with monkeypox, caused by monkeypox virus (MPXV). In May 2019, Singapore notified World Health Organization (WHO) of one laboratory-confirmed case of monkeypox. Considering Singapore is located near Indonesia, awareness about the possibility of an outbreak in Indonesia should be raised. Purpose: To report a case of chickenpox mimicking monkeypox in an adult with diabetes mellitus and acute kidney injury. Case: A 51-year-old male with poorly controlled diabetes mellitus was suspected to have a chickenpox differential diagnosis with monkeypox. His chief complaint was multiple blisters on his body and vomiting. There was a history of feeding a monkey. From dermatological status on facial, trunk, and extremities there were multiple pleomorphic vesicles. Laboratory results showed elevated renal function. Polymerase chain reaction (PCR) examination using VZV as primer revealed a positive result in the range of 810 bp. He was treated with intravenous acyclovir for 3 days and oral acyclovir for 7 days then discharged with improvement in skin lesions and normal renal function. Discussion: Chickenpox in adult and diabetes mellitus patients can give severe clinical manifestation mimicking monkeypox. PCR has a significant role especially when diagnosis could not be established from the physical examination. Acyclovir can be given as the therapy. Conclusion: Adult and poorly controlled diabetes mellitus are important risk factors associated with the severity and complication of chickenpox. A careful diagnostic approach and management are needed.